(untitled) (Research, Society and Development, 2022)
The aim of this study is to report the clinical case of an adult patient with oroantral fistula resulting from extraction, addressing its clinical and surgical aspects. Case Report: A 29-year-old female patient sought care complaining of the passage of liquids and food from the oral cavity to the nasal cavity, in addition to bad breath and pain in the region. She reported that the signs and symptoms appeared one week after the extraction of tooth 16. Previously, she was submitted by another professional for a surgery to slide the vestibular flap to close the communication, but without success. With the presence of an inflammatory and infectious process, pus and air outflow were evidenced by the Valssava Maneuver, the panoramic radiograph confirmed the buccosinusal communication in the posterior region of the maxilla and opacification of the right maxillary sinus. Antibiotic therapy with Amoxicillin and Clavulanic Acid 875mg was instituted. After treatment and disappearance of signs and symptoms, surgery was scheduled to close the bucosinusal communication, using the buccal fat pad in a single procedure. The postoperative period was uneventful and there was follow-up at 1 and 3 months, with favorable healing, without signs of infection and failure. Conclusion: The use of a bichat ball to close oroantral communications is considered an effective alternative, given the high success rate, low risk of infection, comfortable postoperative period, easy access, rich blood supply and generally does not modify the sulcus. entrance exam.